Immature Odonata-Anisoptera in the Iguatemi river basin, upper Paraná River, Mato Grosso do Sul State, Brazil - Boneto, Daiane Dias; Batista-Silva, Valéria Flávia; Soares, Juliane Alessandra Cavalieri; Kashiwaqui, Elaine Antoniassi Luiz; Oliveira, Iana Aparecida Dalla Valle de (Acta Scientiarum. Biological Sciences, 2017)
This study present an inventory of the genera of Odonata-Anisoptera in lotic environments of the Iguatemi River basin, upper Paraná River, Mato Grosso do Sul State, Brazil. Samplings were performed from December 2006 to February 2009 in the Iguatemi River and eight streams of the basin. We collected 739 immature Odonata, distributed in 25 genera and three families; of which one genus represent a new record for the Mato Grosso do Sul State. Progomphus, Tramea, Elasmotemis, Macrothemis, Aphyla and Phylocycla were the most representative genera in the Iguatemi River basin. The genus accumulation curve predicts an increase of new genera for the Iguatemi River basin.